Effets des facons culturales sur la densite des racines et les rendements en grains et en residus de sorgho - Tarawali, G.; Mohamed-Saleem, M.A. (1987)
Studies the effect of ridge height on sorghum production and the benefits associated with ridging including increase in yields of grain and residue and root density.